Radiological risk assessment of a proposed site for a generic VVER-1000 using HotSpot and InterRas codes. (February 2020) - Gyamfi, K.; Birikorang, S.A.; Ampomah-Amoako, E.; Fletcher, J.J.
Abstract: An assessment of radiological risk of a proposed site for a generic VVER 1000 MW nuclear power plant has been conducted using international radiological assessment system (InterRAS) code and HotSpot Health Physics Code in view of Ghana's plan to add nuclear energy to her energy mix. The radiological risk assessment was estimated by considering a hypothetical accident event for a generic VVER 1000 MW at the proposed site. The kind of radionuclides to be release from the fuel meat to the gap between the meat and the clad defined the intervention measures and countermeasures. The available radionuclide for the hottest fuel rod was determined by depleting the core, a method sometimes termed as "source term estimation". The direction of trajectory and Total Effective Dose Equivalent (TEDE) received with the corresponding ground deposition of the released radionuclides were estimated. The right protective actions were determined by estimating the appropriate intervention distances. The maximum TEDE calculated were 3.7 × 10 −1  Sv at 0.1 km and 3.7 × 10 −1 Sv at 0.18 km for InterRAS and HotSpot codes respectively towards the north-east of the release point. Radiological doses of 10 mSv and above was limited to 1.0 km from the point of release. The intervention level for evacuation (50 mSv) ends at 0.5 km for InterRAS code and 0.7 km for HotSpot code. The intervention level for sheltering (10 mSv) also ended at 1.5 km for both InterRAS and HotSpot code. The highest total radionuclide ground deposition was estimated to be approximately 4.0 × 10 6 kBq m −2 at 0.1 km and 3.8 × 10 6 kBq m −2 at 0.18 km for InterRAS and HotSpot respectively. Beyond 5.0 km distance, the ground deposition was in the range of 0.1–1 kBq m −2 . Generally, the estimated annual effective dose for the public was less than the 1 mSv limit, which is the annual allowable limit for the public. Therefore, with respect to the outcome of the estimated results, there wouldn't be any radiological risk above the allowable limit, hence the site can be considered as the candidate site for the construction of the proposed nuclear power plant. Highlights: Radiological risk assessment of NPP site is conducted using HotSpot and InterRAS codes. Direction of the trajectory of the released radionuclides is towards the north-east. The maximum of Total Effective Dose Equivalent occurs within 0.20 km within stability class A. Estimated annual effective dose for the public is less than the 1 mSv regulatory limit. Doses of 10 mSv and above was limited to 1.0 km from the point of release.